(untitled) (Journal of actual problems of jurisprudence, 2019)
The purpose of this article indicate the necessity of further improvement of a state policy in the field of religion at observance of the principles of secular character of the state, fundamental human rights and positive change of a religious situation in the country, preventions and prevention of manifestation of religious extremism among the youth generation. Keywords: extremism, terrorism, youth, prevention.